Ticks on humans in an Atlantic rainforest preserved ecosystem in Brazil: Species, life stages, attachment sites, and temporal pattern of infestation - Suzin, Adriane; da Silva, Marina Xavier; Tognolli, Matheus Henrique; Vogliotti, Alexandre; Adami, Samuel Fernando; Moraes, Marcela Figuêredo Duarte [UNESP]; Nunes, Pablo Henrique; Szabó, Matias Pablo Juan (Elsevier, 2022)
We herein describe exposure and tick attachment to researchers and field staff within the greatest preserved inland Atlantic rainforest, located in Brazil, over a non-consecutive period of five years. Overall, 433 ticks from five species were collected, Amblyomma coelebs (n = 281), Amblyomma brasiliense (n = 79), Amblyomma incisum (n = 43), Amblyomma ovale (n = 4), Haemaphysalis juxtakochi (n = 4). Clusters of larvae belonged to the genus Amblyomma (n = 21) and Haemaphysalis (n = 1). Both Haemaphysalis and Amblyomma species were observed crawling on humans but only ticks from the latter genus were found attached. Most recovered ticks (59%) were found attached and, whereas A. brasiliense was the main host-seeking tick species in the forest, A. coelebs nymphs were the ones that overwhelmingly attached to humans (70% of all attachments). At the same time only 0.4% of human bites were of A. ovale, the Rickettsia parkeri strain Atlantic rainforest vector tick in Brazil. Tick attachment sites were recorded for 132 ticks and lower/upper limbs and the trunk were more parasitized than the head/neck. Tick bites were recorded throughout the year; while larvae did not show an evident seasonal pattern, nymphs attached to humans mainly in autumn and winter and the few adult bites were recorded in spring. Our results highlighted A. coelebs nymphs as major human-biters and evidenced the necessity of studies that discern human tick bites that occur after exposure to host-seeking ticks from those that occur after tick displacement from hosts that carry ticks to human dwellings.
Keywords: Amblyomma coelebs; Exposure risk; Human tick bites; Iguaçu national park; Rainforest; Tick communities